Metabolic and structural changes during early maturation of Inga vera seeds are consistent with the lack of a desiccation phase - Caccere, Rodrigo; Teixeira, Simone P.; Centeno, Danilo C.; Figueiredo-Ribeiro, Rita de Cássia L.; Braga, Márcia R. (Journal of plant physiology, 2013)
Inga vera, native to South America, is an important leguminous species used for ecological restoration of riparian forests and its seeds are among the most recalcitrant ones described up to date. In this work, we analysed the metabolic profile, cell ultrastructure as well as cell wall polysaccharides of I. vera seeds in order to better understand its maturation, which allows embryo germination without a quiescent phase. Increased amounts of citric, glutamic, pyroglutamic, and aspartic acids from stages I to II (120 and 129 days after flowering (DAF)) corroborate the hypothesis of high metabolism, shifting from fermentative to aerobic respiration at seed maturity. This phase was characterized by an extensive vacuolization of embryonic cells, which also indicate high metabolic activity. The proportion of arabinose in the cell walls of embryonic axis (approx. 20%) was lower than those found in some orthodox seeds (nearly 40%), suggesting that arabinose-containing polysaccharides, which are thought to provide more flexibility to the cell wall during natural drying, are less abundant in I. vera seeds. Taken together, our results provide evidence that the major changes occurred during early stages of seed maturation of I. vera, indicating that the rapid temporary metabolic shift observed between stages I and II may be related to the lack of desiccation phase, moving directly to germination.